2015
DOI: 10.1111/eos.12171
|View full text |Cite
|
Sign up to set email alerts
|

Dental fear and previous childhood traumatic experiences, life events, and parental bonding

Abstract: We aimed to determine whether adult dental fear is associated with traumas, life events, and perceived parental bonding. Pilot data for the FinnBrain Cohort study were used. Of the 254 families expecting a baby, 80% agreed to participate. At 32-34 wk of pregnancy, 125 women and 81 men completed a Modified Dental Anxiety Scale questionnaire and were included in this study. Other instruments used were the Trauma and Distress Scale (TADS), the Life Event Checklist, and the Parental Bonding Index. All scales were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
2
9
0
1
Order By: Relevance
“…Although the regression models suggested the impact of familial factors on children’s DFA, the R 2 were low and the models only explained 9.5, 22.4, and 11.7% of the variance in DFA of all subjects, boys, and girls, respectively. This supports the notion that DFA is a complex phenomenon, in which many other factors, such as child’s personality traits [ 43 ], past dental experiences [ 44 ], other life incidents/events [ 45 ], were involved.…”
Section: Discussionsupporting
confidence: 82%
“…Although the regression models suggested the impact of familial factors on children’s DFA, the R 2 were low and the models only explained 9.5, 22.4, and 11.7% of the variance in DFA of all subjects, boys, and girls, respectively. This supports the notion that DFA is a complex phenomenon, in which many other factors, such as child’s personality traits [ 43 ], past dental experiences [ 44 ], other life incidents/events [ 45 ], were involved.…”
Section: Discussionsupporting
confidence: 82%
“…Minority stress often results in a lifetime of harassment, maltreatment, discrimination, and victimization and may ultimately impact access to care . This may increase dental fear levels . Additionally, associations between dental fear and both fear of maltreatment in dental clinics and past maltreatment were significant, which is consistent with previous research among different populations, such as among cisgender adults and children.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, associations between dental fear and both fear of maltreatment in dental clinics and past maltreatment were significant, which is consistent with previous research among different populations, such as among cisgender adults and children. Previous studies reported that even if the maltreatment or discrimination occurred during childhood, long‐term effects impact patients’ dental fear and dental behavior, such as uncooperative behavior during dental treatment and cancellations without notice …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations